Upaya Mempercepat Perkecambahan Benih Kopi Arabika (Coffea arabica L.) Dan Kopi Robusta (Coffea canephora var. robusta) Dengan Penggunaan Air Kelapa - Siti Novridha Andini; Rizka Novi Sesanti (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2018)
Lampung Provinceis one of robusta coffee production center and a small part of arabica coffee production. Coffee plant propagation can be done vegetatively and generatively, to make garden of seeds entres, it is required seeds thatcan be used as rootstock or as a plant propagation. Coffee seeds have long germ time, caused by physical dormancy.Coconut water is one of the natural ingredients, containing hormones like cytokines, auxins and gibberellins that can stimulate germination and plant growth. The purpose of this research is to know the difference of germination time and to get the right coconut water concentration to accelerate the seed germination of Arabica coffee and Robusta coffee, and also to know the interaction between coffee type and coconut water concentration.The research was conducted in August-November 2016, in PlantLaboratory 1 and Green House of Lampung State Polytechnic. Experiments using Completely Randomized Designwith two factors and three replications.The first factor is coffee varieties (K) with two varieties, Arabica Coffee / Sigarar utang (K1) and Robusta Coffee / BP 42 x BP 358 (K2). The second factor is the concentration of coconut water with five concentration, 0% (A0), 25% (A1), 50% (A2), 75% (A3), 100% (A4).Each experiment uses 20 seeds, total seed required for all experiment is 600 seed coffee. The variables observed when sprouts appear, percentage germinated, when cotyledon rupture, simultaneity grow (KST) and growth speed (KCT). The result of variance analysis showed that the treatment of coffee varieties only had a significant effect on the observation variables when sprouts appear, cotyledon rupture, and the simultaneity grow, whereas the coconut water concentration treatment had no significant effect on the whole observation variable. Test results of LSD α 5% Arabica coffee varieties more quickly sprouts appear, cotyledon rupture and the simultaneity grow than Robusta coffee.